GABAergic and glutamatergic transmission reveals novel cardiovascular and urinary bladder control features in the shell nucleus accumbens - de Carvalho, Rodrigo P.; do Vale, Bárbara; Dsouki, Nuha A.; Cafarchio, Eduardo M.; De Luca, Laurival A. [UNESP]; Aronsson, Patrik; Sato, Monica A. (Elsevier, 2023)
The shell Nucleus Accumbens (NAcc) projects to the lateral preoptic area, which is involved in the central micturition control and receives inputs from medullary areas involved in cardiovascular control. We investigated the role of GABAergic and glutamatergic transmission in the shell NAcc on intravesical pressure (IP) and cardiovascular control. Male Wistar rats with guide cannulas implanted bilaterally in the shell NAcc 7 days prior to the experiments were anesthetized with 2% isoflurane in 100% O2 and subjected to cannulation of the femoral artery and vein for mean arterial pressure (MAP) and heart rate recordings (HR) and infusion of drugs, respectively. The urinary bladder (UB) was cannulated for IP measurement. A Doppler flow probe was placed around the renal arterial for renal blood flow (RBF) measurement. After the baseline MAP, HR, IP and RBF recordings for 15 min, GABA or bicuculline methiodate (BMI) or L-glutamate or kynurenic acid (KYN) or saline (vehicle) were bilaterally injected into the shell NAcc and the variables were measured for 30 min. Data are as mean ± SEM and submitted to Student́s t test. GABA injections into the shell NAcc evoked a significant fall in MAP and HR and increased IP and RC compared to saline. L-glutamate in the shell NAcc increased MAP, HR and IP and reduced RC. Injections of BMI and KYN elicited no changes in the variables recorded. Therefore, the GABAergic and glutamatergic transmissions in neurons in the shell NAcc are involved in the neural pathways responsible for the central cardiovascular control and UB regulation.
Keywords: Arterial pressure; Heart rate; Intravesical pressure; Renal blood flow; Shell nucleus accumbens